2018
DOI: 10.7287/peerj.preprints.27057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronological age, biological age, and individual variation in the stress response in the European starling: A follow-up study

Abstract: The responsiveness of the avian stress system declines with age. A recently published study of European starlings (Sturnus vulgaris) found that a marker of biological age predicted stress responsiveness even in individuals of the same chronological age.Specifically, birds that had experienced greater developmental telomere attrition showed a lower peak corticosterone response to an acute stressor, and more rapid recovery of corticosterone levels towards baseline. Here, we performed a follow-up study using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Third, we investigated the direct effects of developmental treatments (the amount of food and the level of begging effort) on impulsivity in the current cohort of birds. Although the two previous starling studies (Bateson et al 2015 ; Nettle et al 2015a ), in line with evidence from other systems (Lovic et al 2011 ; Brydges et al 2015 ), found no direct effects of developmental treatments on impulsivity, in the present cohort of starlings, there is other evidence for direct treatment effects on adult behavioural phenotype (Neville et al 2017 ; Gott et al 2018 ). This may be because the developmental treatments in the current birds, who were hand-reared, were better controlled than earlier cross-fostering manipulations.…”
Section: Introductionsupporting
confidence: 85%
“…Third, we investigated the direct effects of developmental treatments (the amount of food and the level of begging effort) on impulsivity in the current cohort of birds. Although the two previous starling studies (Bateson et al 2015 ; Nettle et al 2015a ), in line with evidence from other systems (Lovic et al 2011 ; Brydges et al 2015 ), found no direct effects of developmental treatments on impulsivity, in the present cohort of starlings, there is other evidence for direct treatment effects on adult behavioural phenotype (Neville et al 2017 ; Gott et al 2018 ). This may be because the developmental treatments in the current birds, who were hand-reared, were better controlled than earlier cross-fostering manipulations.…”
Section: Introductionsupporting
confidence: 85%
“…The premise of this approach is that somatic damage and repair, which determine biological age, often result from physiological processes that are associated with affective states, such as stress or happiness. Indeed, adverse conditions such as sibling competition have been shown to lead to accelerated biological aging limited to the study period, especially when the individual is a weaker competitor (Gott et al, 2018). Surveying population-level variation or tracking individual longitudinal variation in the biological-to-chronological age ratio, through measurements such as telomere length, could be a cost-effective way to estimate relative age-specific welfare within wild populations.…”
Section: Discussionmentioning
confidence: 99%
“…CORT profiles were measured from the same 31 birds when they were aged 127–134 days (methods described in Gott et al 2018 ; the data used here are ‘age point 1’ from that study as this is the closest in age to the judgement bias experiment). Briefly, we used a standardised capture-handling-restraint protocol employed previously in European starlings (Andrews et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The three judgement bias variables were correlated with each of baseline CORT, peak CORT and ΔCORT. Correlations involving peak CORT were partial, controlling for baseline CORT, and correlations involving ΔCORT were partial, controlling for CORT at 15 min (see Gott et al 2018 ). An alpha level of significance of P < 0.05 was used throughout.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation